Valle del Cauca and its challenges in the integral management of wastewater in times of crisis (2021)
Nutrients recovery from wastewater treatment has become a focus of research, since it allows minimizing negative environmental impacts associated with obtaining and eliminating nutrients such as nitrogen and phosphorus. Likewise, it is an alternative to obtain a product with a potential for use in different industrial and agro-industrial sectors. This paper presents the analysis of alternatives for the use of a struvite-rich sludge obtained from municipal wastewater treatment in Valle del Cauca. The results of our research showed that it’s possible to use, the recovered nutrients as an organ mineral fertilizer for crops such as sugarcane, coffee, banana, technified and traditional corn, citrus, mechanized rice, chontaduro, forest plantations, crops of ornamental plants, and as raw material for Valle del Cauca industries related to the formulation, manufacture and distribution of fertilizers